The Effects of Immersive Multimedia Learning with Peer Support on English Oral Skills (Speaking and Reading) - Muslem, Asnawi; Abbas, Merza (Proceeding of International Conference on Teacher Training and Education, 2016)
The methods of teaching English in Indonesia promote the use of code-switching strategies and have resulted in the widespread practice of pronouncing English words following the structures of the Indonesian language. This study investigated at the effects of the immersive multimedia learning technique with peer support on performance in English in terms of oral production skills in reading and speaking that involved six measures, namely, pausing, phrasing, stress, intonation, rate, and integration without the mediation of the studentsâ first language. It also investigated were the effects on performance by studentsâ achievement. The quasi-experimental 2 X 2 factorial design with pre-test and post-test was employed for the study. The first factor was the strategy of learning, namely the use of immersive multimedia learning with and without peer support, while the second factors comprised achievement in English. 80 first-year university students enrolled in English as a foreign language course were selected for this study and the treatment lasted for eight weeks. Data were analysed using one-way ANOVA. The findings showed that the immersive multimedia learning with peer support group reported significantly better performance in all measures of oral production for reading and speaking. Analyses by achievement showed that the high achievement students in the immersive multimedia learning with peer support group reported significantly better performance in all measures of oral production only for speaking while the low achievement students in the immersive multimedia learning with peer supported group reported significantly better performance in all measures of oral production for reading and speaking. These findings showed that the immersive multimedia technique with peer support reduced the use of code-switching strategies among the students and enabled them to develop oral production skills in English approaching the patterns of native speakers especially among low achievement students.